Alzheimer's Disease: Drug Discovery - Huang, Xudong (Exon Publications, 2020)
Alzheimer's disease is the most common cause of age-related dementia. Alzheimer's disease presents with irreversible cognitive decline, which commences as insidious short-term memory dysfunction and gradually spreads to other cognitive domains, rendering patients mute and non-ambulatory after 10-15 years of progressive course. Unfortunately, there are neither effective preventive measures nor efficacious treatments available for this devastating disease. Such a situation undoubtedly calls for the diversification of druggable targets for Alzheimer's disease and a search for poly-targets or drug combination therapeutic strategies. Contributed by an assembly of clinicians and translational and basic research scientists, this book intends to provide an overview of the current state and future perspectives of Alzheimer's disease drug discovery. It covers the underlying pathogenic mechanisms of Alzheimer's disease and provides a review of Aβ amyloid- and τ protein-targeted immunotherapies, and peptide inhibitors for anti-Aβ amyloidosis. In addition, it also examines therapeutic potentials of various Alzheimer's disease drug targets such as brain metal homeostasis, protein kinase C, the blood-brain barrier, epigenetic therapies, as well as discusses chimeric conjugates, multifunctional ligands, and natural products as interventional approaches. This book will be valuable to healthcare professionals caring for patients, researchers and interested readers as it will provoke thoughts about identifying novel and more efficacious therapeutic agents for Alzheimer's disease and related dementias.